2022
DOI: 10.3390/ijms23158442
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polydatin on the Tumor Microenvironment In Vitro: Studies with a Colon Cancer Cell Model

Abstract: The tumor microenvironment of colon carcinoma, the site at which tumor cells and the host immune system interact, is influenced by signals from tumor cells, immunocompetent cells, and bacterial components, including LPS. A large amount of LPS is available in the colon, and this could promote inflammation and metastasis by enhancing tumor cell adhesion to the endothelium. Polydatin (PD), the 3-β-D-glucoside of trans-resveratrol, is a polyphenol with anti-cancer, anti-inflammatory, and immunoregulatory effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…Specifically, we found that resveratrol treatment led to a decrease in the proportion of senescence-associated β-galactosidase positive cells, a well-established marker of cellular senescence. This finding is consistent with previous studies that have demonstrated the anti-aging effects of resveratrol on the cardiovascular system, including its ability to improve endothelial function and reduce oxidative stress and inflammation [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, we found that resveratrol treatment led to a decrease in the proportion of senescence-associated β-galactosidase positive cells, a well-established marker of cellular senescence. This finding is consistent with previous studies that have demonstrated the anti-aging effects of resveratrol on the cardiovascular system, including its ability to improve endothelial function and reduce oxidative stress and inflammation [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…For example, resveratrol derivatives (CS and DMU-281) exert a marked anti-cancer activity on CRC cells, effectively inducing apoptosis and cell cycle arrest [18,19]. Similarly, the 3-β-D-glucoside of trans-resveratrol exerts anti-proliferative and pro-apoptotic effects on CRC cells by regulating modulation of the tumor microenvironment [20]. Additionally, Lin et al [21] reported that oxyresveratrol inhibits CRC cell migration by regulating EMT and microRNA (miRNAs).…”
Section: Resveratrolmentioning
confidence: 99%